2020
DOI: 10.1186/s12951-020-00716-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal LncRNA–NEAT1 derived from MIF-treated mesenchymal stem cells protected against doxorubicin-induced cardiac senescence through sponging miR-221-3p

Abstract: Background The chemotherapy drug doxorubicin (Dox) is widely used for treating a variety of cancers. However, its high cardiotoxicity hampered its clinical use. Exosomes derived from stem cells showed a therapeutic effect against Dox-induced cardiomyopathy (DIC). Previous studies reported that exosomes derived from mesenchymal stem cells (MSCs) pretreated with macrophage migration inhibitory factor (MIF) (exosomeMIF) showed a cardioprotective effect through modulating long noncoding RNAs/microR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…Exosomes are 30 ∼ 150 nm extracellular vesicles (EVs) and membrane bound nanoparticles that contain bioactive substances like proteins, DNA, RNAs, and cytokines [ 20 22 ]. These bioactive components play key roles in intercellular, intertissue, and cross-species communications [ 20 ] and participate in formation and progression of tumor microenvironment (TME) remodeling, intracellular homeostasis, and drug resistance [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are 30 ∼ 150 nm extracellular vesicles (EVs) and membrane bound nanoparticles that contain bioactive substances like proteins, DNA, RNAs, and cytokines [ 20 22 ]. These bioactive components play key roles in intercellular, intertissue, and cross-species communications [ 20 ] and participate in formation and progression of tumor microenvironment (TME) remodeling, intracellular homeostasis, and drug resistance [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gene modi cation to produce exosomes is cheap, convenient and e cient, compared with electroporation and ultrasound methods. Exosomes derived from genetically modi ed stem cells have been used effectively to repair injured hearts as a new cell-free therapy [34][35][36] 37 . Our previous studies also showed that MIF engineered MSC-derived exosomes can reduce myocardial infarction size and improve cardiac function 9 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-221-3p is a target ceRNA of NEAT1 and its enrichment in aged myocardial tissues could impair myocardium regeneration by suppressing the sirtuin family [ [107] , [108] , [109] ]. MiR-221-3p interacts with the 3′-UTR of Sirt2 to inhibit Sirt2 expression at the post-transcriptional level, and Sirt2 activates AMPK to attenuate age-related cardiac hypotrophy and DOX-induced cardiotoxicity, implying that the exosome/NEAT1/miR-221-3p/Sirt2 pathway attenuates cardiomyocyte senescence [ 110 , 111 ].…”
Section: Noncoding Rnas (Ncrnas) and Acetylation In Cardiotoxicitymentioning
confidence: 99%